ANALYSIS OF SHARIA BANK ANTI-MONEY LAUNDERING PREVENTION STRATEGIES OR COMBATING THE FINANCING OF TERRORISM (AML/CFT) IN MAINTAINING CUSTOMER DATA PRIVACY AND SECURITY IN THE 5G TECHNOLOGY ERA (Case Study On Indonesian Sharia Bank Kc Medan Adam Malik) - Rizky Aditya Ananda; Tuti Anggraini (Jurnal Ekonomi, 2022)
This study aims to find out and see whether there is money laundering, whether the strategy implemented is effective or a data security system strategy. This study used descriptive qualitative method. Data collection techniques using observation and interviews. Based on the results of the study it can be concluded that (1) One of the efforts of PT Bank Syariah Indonesia KC. Medan Adam Malik prevents money laundering by applying the know your customer principle with early detection, namely when a customer opens an account and is equipped with various ways to find out what the customer is doing, how much income per month, from there we can detect earlier if a crime of laundering occurs money. (2) Obstacles in applying the principle of knowing your customer are internal barriers, including the lack of identification and formation of customers. There are external constraints, customers themselves are not honest in providing complete information to the bank, there are employees who look for customer information that is not detailed, and customers who are dishonest when asked about the actual situation, and (3) Maintaining the privacy of customer data anti-money laundering, implementing KYCP (Know Your Customer Principles) based on Bank Indonesia Regulation No. 3/10/PBI/2001 concerning Know Your Customer Principles, c is an effective way to get to know customers who want to save or invest their capital.